SEJARAH PERKEMBANGAN RASM UTSMANI - Dian Febrianingsih (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2016)
Rasmul Quran is one part of the Qu'ran disciplines in which there learn about the writing of manuscripts of the Qur'an is done in a special way, both in the writing-pronunciation pronunciation and letter forms are used. Rasmul Qur'an also known as Ottoman Rasm. Koran Ottoman writing is writing attributed to Uthman ra. (Khalifah to III). The term appears after the completion of the copy of the Koran made by a team formed by Ustman in 25H. By the Ulama way of writing is usually termed the "Rasmul Ottoman". Which is then attributed to the Commander of the Faithful Ustman ra. Scholars disagree on this writing, among them there were found the article to be taufiqi (direct provision of the Prophet), they are based on a history which states that the Prophet explained to one kuttab (scribe revelation) that Mu'awiya on the procedure for the writing of revelation , Among scholars cling to this opinion is Ibn al-Mubarak in his book "al-Ibriz" which narrates the words of his teacher 'Abdul' Aziz al-Dibagh ", that writing contained in Ottoman Rasm all have a stake, like it is known that al- The Qur'an is a miracle so did his writing.Keywords: History, Rasm, MushafUtsmani